2019
DOI: 10.1249/mss.0000000000001882
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Preconditioning, O2 Kinetics, and Performance in Normoxia and Hypoxia

Abstract: Introduction Ischemic preconditioning (IPC) before exercise has been shown to be a novel approach to improve performance in different exercise modes in normoxia (NORM). Few studies have been conducted examining potential mechanisms behind these improvements, and less has been done examining its influence during exercise in hypoxia (HYP). Oxygen uptake and extraction kinetics are factors that have been implicated as possible determinants of cycling performance. We hypothesized that IPC would lead to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…First, Δ[HHb] was greater during RSE in T following IPC. This result is similar to a recent study where increased oxygen extraction (i.e., greater deoxygenated hemoglobin) was observed during a 5 km time-trial in hypoxia following IPC treatment (Wiggins et al, 2019). A larger Δ[HHb] is taken to reflect a greater O 2 utilization in the exercising muscle (Paradis-Deschênes et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…First, Δ[HHb] was greater during RSE in T following IPC. This result is similar to a recent study where increased oxygen extraction (i.e., greater deoxygenated hemoglobin) was observed during a 5 km time-trial in hypoxia following IPC treatment (Wiggins et al, 2019). A larger Δ[HHb] is taken to reflect a greater O 2 utilization in the exercising muscle (Paradis-Deschênes et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Kilding et al ( 2018 ) reported a reduction in V̇O 2 slow component during heavy intensity cycling exercise. Wiggins et al ( 2019 ) reported a significant improvement in deoxyhemoglobin and deoxymyoglobin primary component amplitude during cycling 15% below gas exchange ratio in hypoxia following IP. Based on these studies, it is plausible that IP might also affect the kinetics of the hemodynamic response; however, to the best of our knowledge, no studies have done so.…”
Section: Discussionmentioning
confidence: 99%
“…This non-invasive technique, involving repeated episodes of muscle ischemia followed by reperfusion at rest, induces transient peripheral hypoxia and can acutely improve maximal exercise capacity (Cruz et al, 2016 ; Salvador et al, 2016 ). For example, IPC improved mean power output during a 60 s cycling sprint, with a greater increase at exercise onset (Cruz et al, 2016 ), and time-trial (TT) performance in cyclists (Paradis-Deschênes et al, 2018 ; Wiggins et al, 2018 ). However, the precise physiological responses and mechanisms associated with these enhancements are still equivocal.…”
Section: Introductionmentioning
confidence: 99%